Apoplastic lipid barriers regulated by conserved homeobox transcription factors extend seed longevity in multiple plant species. Issue 2 (20th May 2021) - Renard, Joan; Martínez‐Almonacid, Irene; Queralta Castillo, Indira; Sonntag, Annika; Hashim, Aseel; Bissoli, Gaetano; Campos, Laura; Muñoz‐Bertomeu, Jesús; Niñoles, Regina; Roach, Thomas; Sánchez‐León, Susana; Ozuna, Carmen V.; et al.
Summary: Cutin and suberin are lipid polyesters deposited in specific apoplastic compartments. Their fundamental roles in plant biology include controlling the movement of gases, water and solutes, and conferring pathogen resistance. Both cutin and suberin have been shown to be present in the Arabidopsis seed coat where they regulate seed dormancy and longevity. In this study, we use accelerated and natural ageing seed assays,  glutathione redox potential measures,  optical and transmission electron microscopy and gas chromatography‐mass spectrometry to demonstrate that increasing the accumulation of lipid polyesters in the seed coat is the mechanism by which the AtHB25 transcription factor regulates seed permeability and longevity. Chromatin immunoprecipitation during seed maturation revealed that the lipid polyester biosynthetic gene long‐chain acyl‐CoA synthetase 2 ( LACS2 ) is a direct AtHB25 binding target. Gene transfer of this transcription factor to wheat and tomato demonstrated the importance of apoplastic lipid polyesters for the maintenance of seed viability. Our work establishes AtHB25 as a trans‐species regulator of seed longevity and has identified the deposition of apoplastic lipid barriers as a key parameter to improve seed longevity in multiple plant species.